Designing high-voltage and high-rate Li1-xNaxCoO2 by enlarging Li layer spacing. (20th May 2018) - Li, Qi; Wu, Kang; Chen, Minmin; Lee, Yu Lin; Chen, Dongfeng; Wu, Meimei; Li, Faqiang; Xiao, Xiaoling; Hu, Zhongbo
Abstract: In our work, a series of Li1-x Mx CoO2 (M = Na, x = 0–0.05) samples are synthesized by the solid-state calcination route. Electrochemical measurements show that high-rate capacities and high-voltage performances receive obvious improvements with an appropriate content of Na-doping. Specially, the capacity retentions of Li0.97 Na0.03 CoO2 and LiCoO2 are 65.6% and 62.7% after the 100 th cycle at 3.0–4.5 V, respectively. The discharge capacity of Li0.97 Na0.03 CoO2 compared with the pristine electrode LiCoO2 is greatly enhanced from 125 to 135 mAh·g −1 at the rate of 5 C and 98 to 120 mAh·g −1 at the rate of 10 C (1C = 140 mA g −1 ) respectively. With the larger radius of Na + substituted for the smaller radius of Li +, it is found that the bond length of LiO is reduced from 2.0801 Å to 2.0781 Å, which is helpful for stabilizing the structure of LiCoO2 and improving the cycle capability at high voltages. At the same time, the inter-planar distance of Li slabs is expanded from 2.5904 Å to 2.59511 Å which can accelerate the diffusion of Li + and improve the rate capacity. Therefore, Na-doped LiCoO2 shows outstanding high-voltage and high-rate performances, and the strategy can also be popularized and applied to other layered cathodes. Graphical abstract: The Na-doped LiCoO2 exhibits excellent electrochemical properties such as high-rate performances (5C and 10C) and high-voltage performances between 4.3 and 4.5 V. With the larger radius of Na + substituted for the smaller radius of Li +, it is found that the bond length of LiO is reduced from 2.0801 Å to 2.0781 Å, which is helpful for stabilizing the structure of LiCoO2 and improving the cycle capability at high voltages. At the same time, the inter-planar distance of Li slabs is expanded from 2.5904 Å to 2.59511 Å which can accelerate the diffusion of Li + and improve the rate capacity. Therefore, Na-doped LiCoO2 shows outstanding high-voltage and high-rate performances, and the strategy can also be popularized and applied to other layered cathodes. Highlights: The Na-doped LiCoO2 showed better high-voltage and high-rate performances. The bond length of LiO is reduced which can stabilizes the structure of LiCoO2 . The Li layer spacing is increased which can improves the diffusion of Li + . The method will be an effective strategy for other layered cathode materials.